Determination of Oil, Fatty Acid, Tocopherol and Antioxidant Properties of Moringa oleifera Seed Oil Varieties for Commercial Plantation - Winthachai, S.; Vaithanomsat, P.; Punsuvon, V. (Asian Journal of Chemistry, 2015)
Moringa oleifera tree has never been successfully produced as the commercial plantation in Thailand due to its unavailability of high oil content varieties. Our present work reports the chemical characterization of 104 varieties of M. oleifera seeds imported from India and collected in Thailand. The M. oleifera seeds were extracted with hexane in Soxhlet extractor for oil content analysis, ranging from 25-40 % wt. The oil was further analyzed for their fatty acid composition by gas chromatography. The result showed that M. oleifera seed oil contained high level of unsaturated fatty acid, especially oleic acid (up to 77.12 % wt), followed by palmitic acid, stearic acid, behenic acid, eicosenoic acid and linoleic acid. Eight varieties of M. oleifera (40.01-41.68 % wt oil) were selected for further commercial plantation and analyzed for their tocopherol (a-tocopherol, g-tocopherol and d-tocopherol) content, total phenolic content and antioxidant activity.